Development Of Knowledge-Based Power System Protection Design Courseware - Othman, Mohammad Lutfi (2004)
Power system protection is a relatively specialized topic that encompasses a large variety of areas from generator protection at the source side to as far as motor protection at the load end. However, the sources for a complete collection of information on power system protections comprising the generator protection, station bus protection, line protection, transformer protection and motor protection are obviously scattered. Having been in the engineering consultancy business for years, it is realized that finding even a fundamental knowledge of a particular protection scheme in the line protection area in a convenient way is somewhat cumbersome. There isn't any interactive multimedia application software that can offer a complete compilation of topics on various power system protections comprising not only theories but also some pertinent industry application recommendations. It is therefore the objective of the project to develop, using an expert system approach, an interactive multimedia courseware to serve as a computer-based training tool in power system protections by integrating technical theories, industrial application recommendations and some specific simulations by which the user has a wide range of choices for obtaining technical information on power system protection. The method involved in designing the courseware revolves around the approach of using an authoring expert system shell Macromedia Director. It provides the facility of blending the power system protection knowledge domain and interactivity knowledge.